A frame‐based EM‐simulation for design of LC oscillator with MoM capacitor banks. Issue 7 (12th April 2017) - Yoo, Sang‐Sun; Lee, Kang‐Yoon
Abstract: This article presents a simulation method for the design of a digitally controlled oscillator (DCO). Electromagnetic (EM) simulations are essential and inevitable for modern LC oscillator design. Although EM‐simulators provide high accuracy, the EM‐simulation time is very long when metal‐oxide‐metal (MoM) capacitors are present. The proposed frame‐based EM‐simulation can significantly reduce the EM‐simulation time even in the presence of MoM capacitors without influencing the accuracy. To verify the proposed method, a DCO was fabricated using a 55‐nm CMOS process. Measurements of the DCO are in good agreement with the frame‐based post‐layout simulation results. In addition, the DCO has good performances with a low power consumption of approximately 0.68 mW.